The effect of corporate social responsibility disclosure and corporate governance mechanisms on earnings management and stock risk: evidence from Public Bank in Indonesia / Idrianita Anis and Ancella A.Hermawan. - Anis, Idrianita; A.Hermawan, Ancella (Accounting Research Institute (ARI), 2017)
This research aimed to examine the effect of corporate social responsibility  disclosure (CSRD) and corporate governance mechanisms (CGM) on earnings management (EM) and stock risk (SRISK).The first proposed model hypothesized that (1) CSRD and CGM have negative effect on SRISK directly. This research also examined whether CSRD and CGM have negative effect on SRISK indirectly through EM, by examining hypothesis  (2) CSRD and CGM have negative effect on EM, and  (3) EM has positive effect on SRISK..The examination was conducted using the context of mandatory  adoption of IAS-PSAK 50&55 (Revised 2006) and macroprudential policy in 2010. This study used 131 bank-year samples that were listed in IDX for 2008-2013. The result explained that it is proven (1a) CSRD has weak negative effect on SR, (1b) CGM has partial negative effect on SRISK, where BCM  has no significant effect on SRISK, while ACM has significant negative effect on SRISK, (2a) CSRD has significant negative effect on EM, (2b) CGM has partially negative effect on EM, where  BCM has no significant effect on EM, while ACM has significant negative effect on EM, (3) EM has positive significant effect on SRISK. The result 2 and 3  lead to conclusion that direct effect of CSRD to SRISK was explained by indirect effect through EM. The overall result shows CSRD and CGM have negative effect on EM, though there are no significant decrease of EM at post period mandatory adoption of PSAK 50 and 55,  yet the evidence found significant lower  SRISK at post period of mandatory adoption of  PSAK 50&55 (Revised 2006) and macroprudential policy.